A clinical and immunological rationale for ultrasonic cavitation use in the complex treatment of infertility in chronic endometritis - Yury A. Sorokin; Oksana A. Gizinger; Viktor E. Radzinsky (IP Berlin A.V., 2022)
Aim.To prove the safety and efficacy of using the ultrasonic cavitation of saline to restore the endometrial receptivity, local immune balance, and antioxidant status in females with chronic endometritis (CE) and a history of reproductive losses. Materials and methods. Fifty females aged 29.957.65 years (range 2338 years) with histologically and immunohistochemically confirmed CE were examined. The control group included 45 female patients aged 28.989.9 years (range 2338 years) with infertility of tubal-peritoneal genesis without histochemical studies confirming CE and with no history of reproductive losses. Transvaginal pelvic ultrasound was used in the study. All the patients had histological, immunohistochemical examination of endometrial scrapings, including quantification of CD138+, CD20+, CD56+, progesterone receptors (PR), and estrogen receptors (ER) in the stroma and glands. The following cytokines were measured in protein-free fractions of uterine cavity contents by ELISA: interleukin (IL)-2, IL-10, IL-8, tumor necrosis factor-, IL-1, interferon-, interferon-. The activity of lipoperoxidation factors and antioxidant system enzymes (catalase, superoxide dismutase, glutathione peroxidase) was detected by spectrophotometry. As a part of the treatment, irrigation of the uterine cavity with sonicated 0.9% sodium chloride solution was applied twice in 6 sessions consecutively within three months. Results. According to transvaginal pelvic ultrasound, the endometrial thickness before treatment was 6.541.2 mm. An increase in endometrial thickness up to 9.02 (7.6210.42) mm in the luteal phase of the next cycle and up to 9.34 (8.1210.56) mm in the two subsequent luteal phases was observed within three months after irrigation of the uterine cavity with sonicated normal saline. The normalization of the ЕR/PR ratio and decrease in CD138+, CD20+, and CD56+ cells in the endometrial stroma and glands were noted. Mature pinopods were revealed in 71.25 (67.2974.46)% of patients, which is 2.95 times more than the respect value before the treatment, 24.55 (21.4327.75)%. After treatment, a recovery of cytokine production was noted: IL-2, IL-10, tumor necrosis factor-, IL-8, IL-1, interferon-, interferon-; concentration of primary, secondary and tertiary products of lipoperoxidation decreased; superoxide dismutase enzyme activity increased by 36.98 (32.8841.18)%, catalase by 15.32 (14.1316.51)%, glutathione peroxidase by 12.32 (11.1214.2)%; р0,005. Reduced colonization rate of Streptococcus spp, Enterococcus faecalis, Escherichia coli, elimination of Mycoplasma genitalium, Ureaplasma urealyticum, and increased of Lactobacillus spp. were reported. Conclusion. Using the cavitated normal saline restores the endometrium structure, normalizes the ЕR/PR ratio, reduces the colonization by opportunistic and pathogenic microorganisms in the uterine cavity and normalizes the cytokine balance and the content of pro-oxidative and anti-oxidative factors. High clinical and immunological efficacy supports cavitated solutions in the complex treatment of infertility in females with CE.